Theological Study of The Doctrine of The Trinity of God - Waruwu, Sabarani; Terasa Duha; Dapot Damanik; Elisamark Sitopu (Tinta Emas Institute, 2025)
The Doctrine of the Trinity is teachings central in Christian theology states that Lord is one, but consists of from three personal: Father, Son (Jesus Christ), and the Holy Spirit. Although the term